What Else Matters? Competency of Malaysian Educators in Technical and Vocational Education: A Scoping Review - Saipudin, Nurul Ain; Suhairom, Nornazira (Online Journal for TVET Practitioners, 2021)
This article reported up-to-date studies on competencies issues of TVET educators from Malaysia’s institutions. Various electronic databases were used and through systematic selection, 12 scientific articles were identified. The findings of the identified studies were organized by five emerging key matters (1) imbalance of technical and non-technical competency; (2) lack of practical skills training and work experience; (3) issue of greening TVET; (4) lack of self-concept and self-confidence in improving performance; and (5) lack of pedagogical approach for social and humanity competency. This review indicates that these five key matters about competency apply to the current norm of Malaysian TVET educators across all ages. Thus, the review concludes by suggesting educators to progressively increase their knowledge and skills through theoretical and practical training and real experiences acquired from home and abroad. This will enhance their competencies in line with the national and international core standards, that aim to produce skilled, knowledgeable, and high-quality workforces in various TVET industries.